EFFICIENCY OF THE REHABILITATION GAME SYSTEM IN THE PHYSICAL THERAPY OF PATIENTS AFTER ISCHEMIC STROKE (Physical Culture and Sport: Scientific Perspective, 2024)
Today, in Ukraine, as well as in other countries of the world, there is a tendency towards an increase in the number of neurological diseases, in the structure of which acute disruption of cerebral blood circulation is the most relevant and socially significant. The purpose of the study: to determine the effectiveness of the rehabilitation game system in the occupationaltherapy of patients after an ischemic stroke. Research methods: theoretical analysis and generalization of scientific and methodological literature, functional tests of patient assessment (MOCA, Fugl-Meyer, Box&block, 9 hole peg test), pedagogical experiment, methods of mathematical statistics. Work results. The result of testing patients on the Montreal Scale of Cognitive Functions significantly improved over the course of the study by 9.65 points (p < 0.001) in patients with ischemic stroke. During the study, Fugl-Meir test scores improved significantly by 21.42 points (p 0.05). Conclusions. Thus, game rehabilitation systems are effective tools for improving motor functions, coordination and cognitive processes in patients with ischemic stroke. They may also provide new opportunities for research on motor learning and neuroplasticity in the context of rehabilitation.
Keywords: stroke; upper extremity; game rehabilitation system; physical therapy